PEMANFAATAN PASIR NAMBO SEBAGAI BAHAN CAMPURAN LAPIS TIPIS ASPAL PASIR (LATASIR) KELAS B - Dedi Indra Purnomo; Umran Sarita; Muhammad Syarif Prasetia (PRODI D3 TEKNIK SIPIL, 2017)
Abstract The latasir mixture using nambo sand and cemet tonasa as filler in the mixture is expected to obtain flexibility. For for that the aggregate characterisrtics and composition of the mixture must meet the specifications. The method used in this study using trial and error method is by making some specimens to be sampled. Methods of research aggregate testing , asphalt test and manufacture of specimSens on asphalt mixture with variation of bitumen content le 5,0%,5,5%,6,0%,6,5%,7,0%,7,5%,8%,8,5%,9%. Based on the results obtained from the aggregate sieve analysis data for Latasir mixture composition ie Sand nambo = 90% and Semen Tonasa Filler =1in 0%. In The Marshall mixture of Latasir between Pasir nambo and Semen Tonasa, the value of Asphalt Optimum (KAO) was 8.5%.